DAMPAK COVID-19 TERHADAP KEGIATAN PENANGKAPAN BAGAN DI PERAIRAN BAGIAN TENGGARA SULAWESI TENGGARA - Rita L. Bubun; Amir Mahmud; Rosdiana Rosdiana (Bogor Agricultural University, 2022)
Fishing activities using lift net fishing gear has showed a declining trend since COVID-19 pandemic in early 2020. This research aims to identify the impact of COVID-19 on lift net fishing activities in the southeastern waters of Southeast Sulawesi Province in terms of biological, ecological, technological, economic and social aspects. This study applied a survey method to collect data. A quantitative descriptive analysis was carried out to determine the value of the studied aspects by using the Ecosystem Approach to Fisheries Management (EAFM) approach. The results showed that the pandemic impacts on lift net fisheries in biological, ecological, and technological aspects were categorised as unfavourable impacts with the score is ranging from 31 to 38. Meanwhile, the remaining aspects were classified as a good impact scoring between 69 and 86. Accordingly, the policy making process should be conducted by the local government to develop sustainability of the lift net fisheries in the Southeast Sulawesi. Keyword: lift net, COVID 19, EAFM